If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(12 + -1x) = 4 + 5X (12 * 3 + -1x * 3) = 4 + 5X (36 + -3x) = 4 + 5X Solving 36 + -3x = 4 + 5X Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-36' to each side of the equation. 36 + -36 + -3x = 4 + -36 + 5X Combine like terms: 36 + -36 = 0 0 + -3x = 4 + -36 + 5X -3x = 4 + -36 + 5X Combine like terms: 4 + -36 = -32 -3x = -32 + 5X Divide each side by '-3'. x = 10.66666667 + -1.666666667X Simplifying x = 10.66666667 + -1.666666667X
| (-2)-9=-11 | | 10n+n^2=72 | | 12-1/3x=18 | | -5x+3=2x+17 | | 6(6)=17 | | 12-(163/15) | | p-4px/p | | 4n+2n=12 | | 3=p+3-1 | | 13b-9=4b-63 | | -18n-30n=-18-10n | | 4=2x-3y | | -17=6b-7+8 | | 5x+2x-14=28 | | 2(x+2)=x-7 | | 1/3*2-4 | | -10=8b+8-5b | | 6+4n+5=-13 | | 1+4n+5=2 | | b/3-4 | | 18n-30n=-18-10n | | 1/3x0 | | 6x+5x-4x-5=23 | | 10=k+2-2k | | 3x+2(x-5)=c+6 | | 9=2n+n | | 2(x-4)+x=4x+5 | | n-3+8=4 | | -7n+7-7=21 | | -7x-3x=0 | | 15=-n+6n | | 7x+24=x+48 |